Welcoming the Islamic New Year in the Midst of Togetherness in the Tradition of Youth Pilgrimage to 3 Tombs of the Elders of the Ulama of the Hamlet in Pesawahan Village to Strengthen Ties - Ayu Fauziah Annisa Putri; Khairunisa Khairunisa; M. Marteen Ilham Gunawan; Reriz Salwa Faya Aulia; Uput Purwaningrum (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The purpose of this writing is the result of community service in Pesawahan Village while providing benefits to the community, especially in Pesawahan Village, regarding the tradition of commemorating the Islamic New Year. The method used in this study is qualitative. Data collection techniques are taken by interviewing the parties involved and documentation. So the next step that the researcher takes is to check the clarity of the data that has been obtained, compile the data according to the specified writing systematics, and conduct further analysis. The results of this writing are that traditions are widely carried out in regions of Indonesia and these areas have their own characteristics in Pesawahan. This tradition is carried out to commemorate the Islamic New Year with the aim of establishing friendship and making the community close in togetherness, this causes the community to live in harmony.